Keanekaragaman Spesies dan Zonasi Habitat Echinodermata di Perairan Pantai Semerang, Lombok Timur (Diversity of Species and Habitat Zonation of Echinoderm in Semerang Coastal Waters, East Lombok) - Noar Muda Satyawan; Yusli Wardiatno; Rahmat Kurnia (Universitas Mataram, 2014)
Research was conducted in order to determine the diversity of species and habitat zonation of Echinodermata in Semerang coastal waters East Lombok. The field survey was conducted using transects kuadrad and free collection during March to June 2013. Based on the results, in the Semerang Coast was found 26 species of Echinoderm which consist of Echinoidea (13 species), Asteroidea (7 species), Ophiuroidea (3 species ) and Holothuroidea (3 species). Echinoderms habitat in Semerang divided into 5 zones, consist of reef flat, sand, seagrass beds, rubble, and coral reefs. Diversity index values differ in each habitat. Shannon - Wiener index (HÃªÅ¾Å) were largest on coral reef habitats (H ÃªÅ¾Å = 2.59 )and then followed by sand (H ÃªÅ¾Å = 2.30), rubble (H ÃªÅ¾Å = 2.17), seagrass (H ÃªÅ¾Å = 1, 93) and the reef flat (H ÃªÅ¾Å = 1.48). Greatest Evenness index was found in the sand habitat (E = 0.96) followed by a reef flat (E = 0.92), coral reefs (E = 0.86), rubble (E = 0.75) and seagrass beds (E = 0.67). the largest found Margalef Index (R), was found in coral reef habitats (R = 5.02) and then followed by rubble (R = 4.07), sand (R = 3.79), seagrass bed (R = 3.62) and reef flat (R = 1.41). Class of Echinoidea has found in all zones, Asteroidea and Holothuroidea not found on the reef flat zone while Ophiuroidea only found in the rubble and the coral reef zone.